Ефективність психологічної підготовки працівників заводу «Дніпроспецсталь» на рівень комфортності взаємодії з лікарем стоматологом - Возна, Ірина Володимирівна; Возная, И. В.; Vozna, I. V. (Українська медична стоматологічна академія, 2019)
Стаття присвячена аналізу результатів соціологічного дослідження серед лікарів стоматологів з приводу свого відношення до психологічної підготовки пацієнтів. В статті представлені результати оцінки стоматологами ефективності психологічної підготовки пацієнтів на рівень комфортності взаємодії з лікарем стоматологом. Використання лікарями стоматологами різних спеціальностей в своїй практиці психологічної підготовки пацієнтів дозволяє усунути проблеми взаємодії між лікарем та пацієнтом, що сприятиме ефективному процесу лікування. Статья посвящена анализу результатов социологического исследования среди врачей стоматологов по поводу своего отношения к психологической подготовке пациентов. В статье представлены результаты оценки врачами стоматологами эффективности психологической подготовки пациентов на уровень комфортности взаимодействия с врачом стоматологом. Использование врачами стоматологами разных специальностей в своей практике психологической подготовки пациентов позволяет устранить проблемы взаимодействия между врачом и пациентом, что будет способствовать эффективному процессу лечения. The article is devoted to the analysis of the sociological research’s results among the dentists concerning their attitude to the psychological preparation of the patients. The aim of this work was to evaluate the effectiveness of psychological training of «Dniprospetsstal» employees on the comfort level of interaction with the dentist. In order to achieve the goal of the study, we conducted a survey of 117 dental specialists on the psychological training’s impact on the comfort of the patient’s interaction with the dentist. The effectiveness of psychological training of plant workers was evaluated by 58 (49.6%) dentists-therapists, 42 (35.9%) dentists-orthopedists, 17 (14.5%) dentists-surgeons. Among the respondents, men were 53 (45.3%), women respectively were 64 (54.7%). We have developed questionnaires, which were filled by a dentist after the second or the third patient admission, namely, after the conducting of our specially presented methodics of psychological preparation of the patients by the doctors. In our study, we asked the respondents to evaluate «How clearly and accessibly» the method of psychological training was presented. «Almost everything is understood», or «All is understood» is considered by 92 (78.6%) dentists, namely 60 (65.2%) women and 32 (34.8%) men. Women were more comfortable with this technique. The choice of the answer was influenced not only by the gender of the specialists, but also by the experience of work. The longer the doctor’s work experience was, the more positive was the answer. Thus, the dentists with work experience of 16-21 years and over 58 (49.6%) said that «Everything is clear», with experience of work from 5 to 15 years 47 (40.2%) – «Almost everything is clear». Only 12 (10.2%) specialists with up to 5 years of experience had the problems of mastering the technique. Analyzing the answers to the question «What are the difficulties?» we noticed, that a small number of specialists 13 (11.1%) had problems with the concept understanding at all. In determining the type of patient, young doctors generally had difficulties. 58 (49.6%) dentists with work experience of 16 years and over had difficulty adjusting their behavior to the type of the patient. We were interested in how simply the experts used this technique in their practical activity. Almost all women and 36 (67.9%) men easily used this technique in their work. Dentists-surgeons noted, that they have difficulties, and dentists-therapists and orthopedists are ready to introduce psychological preparation of the patients into the daily practical activities. A smaller contingent of physicians 34 (29.1%) said they were ready to master this technique. Determining the patient’s type is an important index in conducting psychological training. The correct choice of the patient’s type depends on the individual approach. Specialists with more than 16 years of experience in 49.6% of cases (58 specialists) confidently determined the patient’s type and spent about seven minutes. More than ten minutes the type of the patient were determined by 59 (50.4%) specialists, who have been working not more than 15 years. According to our observations, women spent about 5 minutes determining the type of the patient, that is much less than men. According to women 48 (75.0%), it was most difficult to work with a strong-willed and idealistic type of the patients. And 43 men (81.1%) considered provocative patients as «severe». For women, the most «light» patients were feeling and provoking, according to 52 (81.2%) interviewed. For men were idealistic and sensitive type, there were 41 (77.4%) answers. Experience has had some influence on the choice of «heavy» and «light» patients. For 12 (10.2%) doctors with experience up to 5 years, the provocative patients were as «severe», and for 34 (29.1%) doctors with experience of work 21 years and more were the patients of willed type. The most «light» patients, both in young and in experienced specialists, were the patients of sensitive type. We are very pleased, that 102 (87.2%) of the interviewed respondents consider given method of psychological training as an important and necessary in mastering communication skills with different groups of the patients. We were saddened by the fact that, in 12.8% of colleagues, this technique did not improve communication with the patients. These were men with work experience up to 5 years, specializing as orthopedic dentists and dental surgeons. Conclusions. Thus, professionals providing dental care to workers with adverse conditions of manufacturing, positively assessed the possibilities of psychological training on the success of interactions with different groups of the patients. The use of the patients’ psychological preparation by dentists of different specialties in their practice eliminates the problems of interaction between the doctor and the patient, which will facilitate an effective treatment process.
Эффективность психологической подготовки работников завода «Днепроспецсталь» на уровень комфортности взаимодействия с врачом стоматологом
Effectiveness of psychological training of «Dniprospetsstal» plant employees on the comfort level of interaction with a dentist
Keywords: психологічна підготовка; взаємодія; стоматологічна допомога; психологическая подготовка; взаимодействие; стоматологическая помощь; psychological preparation; interaction; dental care